Effects of crystallization conditions on dielectric and ferroelectric properties of PZT thin films - Araujo, E. B.; Eiras, J. A. (Iop Publishing Ltd, 2003)
This paper reports studies on dielectric and ferroelectric properties of lead zirconate titanate (PZT) thin films crystallized by conventional thermal annealing (CTA) and rapid thermal annealing (RTA) in air, oxygen and nitrogen atmospheres to better understand, control and optimize these properties. The dielectric constant (epsilon) and dissipation factor (tan delta) values, at a frequency of 100 kHz; for film crystallized in air by CTA process, were 358 and 0.039, respectively. Considering the same frequency for film crystallized in air by RTA, these values were 611 and 0.026, respectively. The different dielectric values were justified by a space-charge or interfacial polarization in films, often characterized as Maxwell-Wagner type. This effect was also responsible to dispersion at frequencies above 1 MHz in film crystallized in air by CTA process and film crystallized by RTA in oxygen atmosphere. The film crystallized by RTA under nitrogen atmosphere presented an evident dispersion at frequencies around 100 Hz, characterized by an increase in both epsilon and tan delta. This dispersion was attributed to conductivity effects. The remanent polarization (P-r) and coercive field (E-c) were also obtained for all films. Films obtained from RTA in air presented higher P-r (17.8 muC cm(-2)) than film crystallized from CTA (7.8 muC cm(-2)). As a function of the crystallization atmospheres, films crystallized by RTA in air and nitrogen presented essentially the same P-r values (around 18 muC cm(-2)) but the P-r (3.9 muC cm(-2)) obtained from film crystallized under oxygen atmosphere was profoundly influenced.